以安全、節能及遊憩為目的之車載網路系統---子計畫三：車載網路之位置感知服務---設計一個結合汽車及自行車行動導覽遊憩之系統(I) - 曾煜棋; TSENG YU-CHEE (My University, 2009)
本子計畫希望透過車載網路系統、並結合汽車與自行車導覽遊憩，以提供使用者位置感知服務。為了配合總計畫「以安全、節能及遊憩為目的之車載網路系統」以及應用其他子計畫所開發的技術，本子計畫將預期設計一套結合汽車與自行車行動之導覽遊憩系統；本子計畫有兩大研究方向：第一個研究方向是開發針對車載網路系統上之位置感知服務，目標是希望於車載裝置上，除了提供準確定位的服務外，甚而可獲得其他位置相關資訊；我們初期以建立樣本比對之定位系統作為無線通訊網路定位的基礎，之後將結合該樣本比對技術與現有成熟的全球定位系統(GPS)，以開發一套「混合型的全球定位系統」，該系統能夠隨時提供行動使用者正確且穩定的位置資訊，由於定位技術需要樣本位置訊號的訓練，如何有效結合車載網路、並利用汽車提供此訓練將是一大挑戰；之後，我們將基於Web 2.0的精神開發一套地理指紋社群系統，這是一套倚賴分享精神所建構的軟體定位平台，基於這個平台，我們預期將開發多個位置感知服務，例如：Geo-Ads(即時商家廣告)、Geo-Parking(附近停車資訊)、Geo-Search(搜查商家)等生活應用；最後，我們將透過車載網路系統存取這些應用，並結合到汽車與自行車導覽遊憩中。第二個研究方向是針對汽車與自行車導覽遊憩相關之案例研究，目標希望能實現以遊憩、甚而是節能的汽車及自行車的導覽遊憩系統，首先為了配合推廣自行車旅遊，我們會先針對營運面還有交通面進行調查，進而開發一套完善的自行車租借營運系統，再來是結合車載網路之位置感知服務於自行車觀光導覽上，以其使自然生態得到保護、遊憩需求得到滿足。 在為期三年的計畫期間中，我們將針對上述兩大研究方向開發相關的核心技術與實作系統；在第一年度中，我們將研發重要的定位核心技術，包括以車載網路系統為基礎的樣本比對技術、混合型的全球定位系統、以及在車載系統上提供定位與慣性導航，此外，我們將深入研究並分析目前國內外對於自行車遊憩與租借系統之案例分析，包括需求/交通/通訊面的調查，以及改變模式應用的研究。有了第一年度的定位核心技術與自行車遊憩與租借系統成功案例之分析，在第二年度中，我們將開發一系列的位置感知服務以及開發自有的自行車遊憩與租借系統，在位置感知服務方面，我們將設計地理指紋社群系統平台、並於其上開發多個生活應用，最後即可透過車載網路系統存取該平台，以便讓使用者順利取得想要的位置感知服務；在開發自有的自行車遊憩與租借系統的方面，我們將結合CHC開發的技術，研發一套低成本、人性化、高營運性的自行車遊憩與租借系統，而其中CHC的技術包含了智慧型雙辨識系統技術、防竊裝置機電控制系統技術、以及參數式安全監控管理系統技術。最後，在第三年度當中，我們將與新竹縣綠世界生態農場合作，把車載位置感知服務以及所開發的自行車遊憩與租借系統應用在汽車、自行車、與步行之導覽遊憩，這年度的工作目標除了基本的網路與相關設備之佈建與園區的導覽內容之建置外，我們預期提供汽車、自行車、與行人之位置感知與導覽遊憩之服務，並提供使用者於車載定位平台上選取綠世界園區的個人化之數位旅遊日誌服務。

The objective of this sub-project is to provide location-based services (LBS) by combining vehicular networks with guiding and recreation for car and bike tours. In order to follow the ultimate goal of the main project, “An Advanced Telematics System for Safety, Energy Conservation, and Recreation” and cooperate with other sub-projects, we would like to design a mobile guiding and recreation system for car and bike tours. There are two important research topics as follows. The first topic is to develop LBS in vehicular networks to provide not only precise location information but also many value-added location-related services. We will design pattern-matching localization as the basis technique of wireless localization. Then, we will combine the wireless localization and the Global Positioning System (GPS) to a hybrid-GPS system, which can provide mobile users correct and stable location information at any-time, anywhere. It is a big challenge to use cars to collect sampling data for localization training phase and communicate through vehicular networks. After that, we will construct a Geo-Fingerprint community platform based on Web 2.0 technology, and we hope to develop some LBS, such as Geo-Ads, Geo-Parking, Geo-Search, and etc., over this platform. Finally, mobile users can access these LBS for guiding and recreation through vehicular networks. The second topic is to investigate some cases of guiding and recreation for car and bike tours. The goal is to develop a guiding system, which is designed for the purpose of recreation and even energy-conservation, for car and bike tours. First of all, to cooperate with the goal of popularizing the bike tours, we will conduct a survey on the business operation and traffic sides and then establish a complete bike-renting system. Then, we will integrate LBS in vehicular networks into bike tours, which can protect our environment from being polluted, and accomplish our recreation requirement at the same time. We will focus on the topics described above to design core localization technologies and implement vehicular communication platform. In the first year, we will design a series of localization core technologies and study cases of bike recreation and renting system. In the second year, a series of LBS are developed based on the Geo-Fingerprint community platform, and mobile users can access some LBS over vehicular networks. Then, we will integrate CHC technology to construct a bike-renting system. In the last year, we will implement our system model in Green World in Hsin-chu country, and we will provide cars, bikes, and people location-based and guiding services over vehicular networks.
Location-Based Services in Vehicular Networks---Mobile Guiding and Recreation for Car and Bike Tours(I)
Keywords: 車載網路; 位置感知服務; 定位; 行動導覽遊憩; 自行車旅遊; Vehicular Networks; Location-Based Service; Localization; Mobile Guiding and Recreation; Bike Tours